PENERAPAN METODE KANSEI ENGINEERING UNTUK PENINGKATAN DESAIN WEBSITE SEKOLAH SMK MUHAMADDIYAH KAWALI - Febrian; Sidiq, Maulana; Maulana, Haisyam (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The rapid development of information technology has driven educational institutions to present digital media that is both informative and representative, such as school websites. However, the user interface design of the SMK Muhammadiyah Kawali website is considered suboptimal in terms of aesthetics and user comfort. This study aims to improve the website’s user interface using the Kansei Engineering Type I method, which focuses on translating users’ emotions and perceptions into design elements. The research process involved identifying Kansei Words, developing questionnaires using a Semantic Differential Scale, collecting data from IT teachers, vocational students, and Information Systems students at Universitas Galuh, and analyzing the data using multivariate statistical methods such as CCA, PCA, FA, and PLS. The results indicate that several visual elements of the website can be optimized to create a more emotionally engaging, user-friendly, and school-representative interface. This study produces new interface design recommendations in the form of wireframes and Mockups, expected to enhance the user experience of the SMK Muhammadiyah Kawali website.